1996
DOI: 10.1017/s0950268800052456
|View full text |Cite
|
Sign up to set email alerts
|

Pigs experimentally infected withSerpulina hyodysenteriaecan be protected from developing swine dysentery by feeding them a highly digestible diet

Abstract: SUMMARYWeaner pigs (n = 72) were fed 1 of 4 diets. These were based on either cooked rice and animal protein, cooked rice and lupin, wheat and lupin, or wheat and animal protein. Twenty-six of the pigs were slaughtered after 1 month. Those fed the highly digestible cooked rice and animal protein diet had drier colonic contents and faeces, lighter large intestines, and the contents of their large intestines had increased pH values and decreased total VFA concentrations. The other 46 pigs were orally challenged … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
56
3
4

Year Published

1997
1997
2019
2019

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(70 citation statements)
references
References 33 publications
7
56
3
4
Order By: Relevance
“…Swine dysentery is caused by colonization of the large intestine by the spirochete B. hyodysenteriae. It has been shown that expression of swine dysentery can be reduced by feeding pigs with FLF (19) or diets low in soluble nonstarch polysaccharides, oligosaccharides, and resistant starch (3,29,30,34). The positive dietary effect was suggested to be due to the decreased amount of fermentable substrate reaching the large intestine, thus preventing colonization of B. hyodysenteriae either by direct reduction in the substrate available for the pathogen itself or by inhibition of a synergistic microbiota.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Swine dysentery is caused by colonization of the large intestine by the spirochete B. hyodysenteriae. It has been shown that expression of swine dysentery can be reduced by feeding pigs with FLF (19) or diets low in soluble nonstarch polysaccharides, oligosaccharides, and resistant starch (3,29,30,34). The positive dietary effect was suggested to be due to the decreased amount of fermentable substrate reaching the large intestine, thus preventing colonization of B. hyodysenteriae either by direct reduction in the substrate available for the pathogen itself or by inhibition of a synergistic microbiota.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, the scenario in the proximal part of the gastrointestinal tract seems crucial when considering the antibacterial effect of FLF. It has been suggested, on the other hand, that the amount of fermentable substrate reaching the large intestine can influence expression of Brachyspira hyodysenteriae-mediated swine dysentery (3,29,30,34). The aim of the present study was therefore to analyze microbial response mechanisms in the different parts of the gastrointestinal tract when feeding FLF to pigs.…”
mentioning
confidence: 98%
“…The experimental diets were chosen in an attempt to minimize the frequency of clinical infections with B. hyodysenteriae. Diets based on cooked white rice have been shown to protect pigs against swine dysentery, whereas increasing amounts of dietary fibers compound the incidents of swine dysentery (22,29). A proposed mechanism is that the amount of fermentable substrate in the large intestine affects components of the intestinal microbiota that are synergistic with B. hyodysenteriae (8).…”
Section: Discussionmentioning
confidence: 99%
“…Environmental and dietary factors also may be involved. Diet has been shown to influence colonization of pigs with the related spirochaete Serpulina hyodysenteriae [33,34], and the same may apply to S. pilosicoli. Village pigs predominantly scavenge, or are fed raw sweet potato, whereas the commercial pigs were fed a balanced mash feed based on cereals and legumes.…”
Section: Discussionmentioning
confidence: 99%